A fast multiresolution moment-method algorithm using wavelet concepts - Kim, Hyeongdong; Ling, Hao (Microwave and optical technology letters, 1995)
A fast multiresolution moment‐method algorithm is developed based on the spectral‐domain wavelet concept. The computational savings are achieved by taking advantage of the multiscale feature of the spectral‐domain Green's function. It is shown that the multiresolution algorithm leads to reduced computational complexity in the matrix‐vector multiplication operation. © 1995 John Wiley & Sons, Inc.